A scoping review to explore how universal design for learning is described and implemented by rehabilitation health professionals in school settings - Kennedy, J.; Missiuna, C.; Pollock, N.; Wu, S.; Yost, J.; Campbell, W. (Child : care, health & development, 2018)
Background Universal design for learning (UDL) is a framework that provides guidelines to support children with diverse needs in the classroom and promotes inclusion of all children. Although UDL is recognized as a promising approach for school‐based rehabilitation health professionals (RHPs), there are no studies that synthesize evidence on the use of UDL by RHPs in the school setting. Therefore, the research question for this study is: How is UDL described and implemented in school settings by RHPs? This study specifically examined literature from occupational therapy, physiotherapy, and speech‐language pathology. Methods A scoping review was completed to (a) summarize how UDL is described in the rehabilitation literature, (b) summarize the recommended and reported role of RHPs in the delivery of UDL, and (c) identify gaps in the evidence base. CINAHL, Embase, MEDLINE, PsychINFO, Sociological s, Web of Science, and ERIC electronic databases were searched. Numerical summaries and theoretical thematic analysis were used to describe the data both quantitatively and qualitatively. Results Inclusion criteria were achieved for 45 of the 3,998 screened documents. Most of the included documents lacked a definition of UDL. Analysis suggested that speech‐language pathologists and occupational therapists implement UDL in a variety of ways within the school setting. No physiotherapy literature was found, and limited high‐level empirical research has been conducted within rehabilitation. Conclusion This scoping review provides a broad understanding of how RHPs describe and implement UDL‐aligned services in school settings. UDL is a promising framework that provides RHPs with guidance on how to support children with diverse needs in the classroom, with the overall aim to promote inclusion of all children. There is a need for further research to determine the effectiveness of UDL as implemented by RHPs and to examine the role of physiotherapists in using UDL‐type services.